LEGAL ANALYSIS OF CORPORATE LIABILITY TOP INSIDER TRADING PLATFORMS FOR DIGITAL ASSETS IN INDONESIA - Anggi Purnama Tradesa; Angga Dinata (Tahiro : Journal of Peace and Religious Mederation, 2025)
This study aims to understand how the development of financial technology and digital assets in Indonesia has opened new economic opportunities, but has also given rise to new forms of crime, one of which is insider trading in digital asset transactions. This practice poses legal challenges because perpetrators are not always individuals but can also be corporations that control information and transaction systems. This study aims to analyze corporate legal liability for insider trading practices on digital asset platforms in Indonesia. The method used is normative juridical, with a statutory and conceptual approach. The results show that existing regulations still focus on conventional securities transactions, while the legal framework for digital assets still does not provide a clear basis for corporate accountability for insider trading practices.